2015
DOI: 10.4103/2141-9248.165260
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of prenatal intervention on pain and anxiety during the process of Childbirth-Northern Iran: Clinical trial study

Abstract: Background:Due to the painful nature of childbirth and its maternal and neonatal complications, the woman needs support in this phase of their life. Increased knowledge and skills during pregnancy prepares pregnant mothers for labor and leads to promoted health.Aim:This study was designed to evaluate the effectiveness of “prenatal education” on the process of childbirth.Subjects and Methods:This clinical trial was conducted on 195 pregnant women, that is, control group (N = 132) and case group (N = 63) attendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…The birthing process accounts for more than 90% of a woman’s stress and anxiety during prenatal care, mainly related to lack of knowledge and fear of childbirth 23 . The presence of anxiety symptoms was characteristic in the PG (>88%), CG (>88%) and IG (100%) groups, which may be related to the low prenatal education observed in all three study groups (>85%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The birthing process accounts for more than 90% of a woman’s stress and anxiety during prenatal care, mainly related to lack of knowledge and fear of childbirth 23 . The presence of anxiety symptoms was characteristic in the PG (>88%), CG (>88%) and IG (100%) groups, which may be related to the low prenatal education observed in all three study groups (>85%).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety is a common symptom faced by women during labor which is often related to a lack of information about gestation and delivery during prenatal care, or may arise from a new and unknown situation such as birth to first-time mothers 1 . Anxiety disorders and distress experienced by women during gestation may also be related to postpartum depression, premature birth, cesarean delivery and difficulties in raising the children 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beneficial effects identified include shorter delivery time, better detection of labour, fewer interventions, a reduced need for anaesthesia, lower levels of anxiety and greater satisfaction. [4][5][6] Previous studies on pregnancy anxiety from different parts of the world have reported a high and wide-ranging prevalence rate of 14-54%. However, it is likely there is a higher prevalence of childbirth anxiety, even as high as 90-94%, due to poor perceived knowledge and inadequate childbirth preparation for nulliparous pregnant women of our state.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 132 participants, women who attended childbirth classes regularly had more knowledge on childbirth, were confident in their ability to give birth and were involved in the shared decision-making process (Pinar et al, 2018). In another study, women with childbirth education managed labour pain better, used less medications during labour and had less instrumental birth incidences (Firouzbakht et al, 2015;Gluck et al, 2020). Attending childbirth classes was also associated with a positive relationship with the medical staff and more success in breastfeeding (Gao et al, 2019;Lin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%